Corrigenda: The Numerical Reliability of Econometric Software - McCullough, B. D.; Vinod, Hrishikesh D. (Journal of Economic Literature, 1999)
CORRIGENDA Volume 37, June 1999 In "The Numerical Reliability of Econometric Software", by B. D. McCullough and H. D. Vinod, there are misprints in some equations on page 647 in the upper part of the left-hand column. The passage should read as follows: The normal equations are 6?^ + 61.5? ^ = 7.261 61.5?^ + 630.55? ^ = 74.5053 which yields a regression line of Y^ = ?3.478 + 0.457X. Suppose that the normal equations had been computed only to four significant digits as 6?^ + 61.5? ^ = 7.261 61.5?^ + 630.6? ^ = 74.50.